Cultivating Mental Toughness in Traditional Martial Arts: A Qualitative Study of Pencak Silat Practitioners - Muzaki, Ahmad; Saputro, Irwan Adi; Yulianingrum, Diyah; Jariono, Gatot (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2026)
Psychological preparedness constitutes a decisive yet underexplored determinant of competitive excellence in traditional martial arts, particularly within culturally embedded disciplines such as Pencak Silat. Despite growing recognition of mental toughness in sport psychology, empirically grounded, culturally specific frameworks for champion mentality cultivation remain conspicuously absent in existing literature. This study aimed to investigate the strategies, stakeholder roles, and contextual determinants underlying champion mentality formation among Pencak Silat athletes in Boyolali Regency, Central Java, Indonesia. Employing a phenomenological qualitative design with reflexive thematic analysis, data were collected from 26 purposively selected participants, eight certified coaches, and eighteen competitive athletes through semi-structured interviews, structured field observations across twelve training sessions, and documentary analysis. Four principal themes emerged: character-based developmental strategies, multistakeholder roles in mental conditioning, intrinsic-extrinsic determinants of resilience, and adaptive obstacle-management solutions. Uniquely, findings revealed that indigenous philosophical values, budi pekerti (refined character), keselarasan (harmonious balance), and pengendalian diri (self-mastery) do not contradict Western sport psychology frameworks but organically reinforce Self-Determination Theory and Achievement Goal Theory principles. This cultural-psychological convergence constitutes the primary scholarly contribution of this investigation, demonstrating that sustainable mental toughness in Southeast Asian martial arts emerges through habituated character formation rather than episodic motivational intervention. Coaches are recommended to systematically integrate mindfulness-based regulation, cognitive reappraisal strategies, and culturally contextualised reflective dialogue into formal curricula, advancing more globally inclusive models of sport psychology.